MR Imaging of Ventral Thalamic Nuclei - Yamada, K.; Akazawa, K.; Yuen, S.; Goto, M.; Matsushima, S.; Takahata, A.; Nakagawa, M.; Mineura, K.; Nishimura, T. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: The Vim and VPL are important target regions of the thalamus for DBS. Our aim was to clarify the anatomic locations of the ventral thalamic nuclei, including the Vim and VPL, on MR imaging. MATERIALS AND METHODS: Ten healthy adult volunteers underwent MR imaging by using a 1.5T whole-body scanner. The subjects included 5 men and 5 women, ranging in age from 23 to 38 years, with a mean age of 28 years. The subjects were imaged with STIR sequences (TR/TE/TI = 3200 ms/15 ms/120 ms) and DTI with a single-shot echo-planar imaging technique (TR/TE = 6000 ms/88 ms, b-value = 2000 s/mm2). Tractography of the CTC and spinothalamic pathway was used to identify the thalamic nuclei. Tractography of the PT was used as a reference, and the results were superimposed on the STIR image, FA map, and color-coded vector map. RESULTS: The Vim, VPL, and PT were all in close contact at the level through the ventral thalamus. The Vim was bounded laterally by the PT and medially by the IML. The VPL was bounded anteriorly by the Vim, laterally by the internal capsule, and medially by the IML. The posterior boundary of the VPL was defined by a band of low FA that divided the VPL from the pulvinar. CONCLUSIONS: The ventral thalamic nuclei can be identified on MR imaging by using reference structures such as the PT and the IML. ACanterior commissureCcaudate nucleusCTCcerebellothalamocortical tractDBSdeep brain stimulationDTIdiffusion tensor imagingFAfractional anisotropyfMRIfunctional MR imagingIMLinternal medullary laminaPputamenPCposterior commissurePTpyramidal tractPulvpulvinarRNred nucleusROIregion of interestSTsensory tractSTIRshort tau inversion recoveryThthalamusVPLventroposterolateral nucleiVimventrointermediate nuclei